Pregnant adolescents and prenatal adherence: a exploratory study in urban area - Lucia Helena Garcia Penna; Úrsula Pérsia Paulo dos Santos; Helena Maria Scherlowski Leal David (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This article presents the profile of pregnant adolescents accompanied in the prenatal into a University Hospital of Rio de Janeiro, analyzing factors that can be interfering in their adherence. It is a descriptive and quantitative study, with analysis of secondary data. The profile was resembled to the results of other investigations with pregnant adolescents of popular classes in urban areas. The residence places and the distance to the prenatal service was configuring as potential influencers in prenatal adherence, expressing the accessibility to the health services. Thus, we concluded that it is necessary to develop changes in institutional practices able to interfere in the bond between pregnant adolescent and services.